Mewujudkan Kemandirian Ekonomi Desa Melalui Pembangunan dan Pengembangan Potensi Ekonomi Desa Watiginanda - Samsul, Samsul; Gurusi, La; Satria, Eko; Nurcahyo, Edy; Asiri, La; Herianto, Herianto; Nurdin, Nurdin; Jurumai, La Pande; Kurnianto, Dandi; Adilani, La (FAKULTAS TEKNIK UMKENDARI, 2023)
One of the objectives of rural development, as emphasized in Article 78, paragraph (1) of Law Number 6 of 2014 concerning Villages, is to improve the welfare of rural communities and the quality of human life, as well as poverty alleviation through the development of local economic potentials and the sustainable utilization of natural resources and the environment. The development and enhancement of local economic potentials can realize the economic self-reliance of the village. Watiginanda Village needs to undertake strategic initiatives, including the development and improvement of the local economy. Community service is conducted through the method of data collection and mapping of the local economic potentials of Watiginanda Village, which can be built and developed by the village government. In conclusion, Watiginanda Village has local potentials that can elevate its status from a developing village to an advanced village, including agricultural, fisheries, and tourism potentials. Key Word: Self-reliance, development, and local economy